12-Month clinical outcomes of amphilimus drug eluting stents in an all-comers South-East Asian registry. (February 2020) - Ho, Hee Hwa; Sinaga, Dasdo Antonius; Arshad, Mohd Kamal Mohd; Kasim, Sazzli; Lee, Jin Hyun; Khoo, Deanna Zhi Lin; Loh, Kwok Kong; Jafary, Fahim Haider; Ong, Paul Jau Lueng; Lo, Simon Soo Siong
Abstract: Background: Amphilimus-eluting stent (AES) is a novel polymer-free drug eluting stent that combines sirolimus with fatty acid as antiproliferative drug and has shown promising results in percutaneous coronary intervention. We evaluated the clinical safety and efficacy of AES in an all-comers South-East Asian registry. Methods: Between May 2014 to April 2017, 268 patients (88% male, mean age 60.1 ± 10.8 years) with 291 coronary lesions were treated with AES. The primary endpoint was major adverse cardiac events (MACE) ie a composite of cardiovascular mortality, myocardial infarction (MI) and target lesion revascularization (TLR) at 12-month follow-up. Results: The majority of patients presented with acute coronary syndrome (75%) and 75% had multi-vessel disease on angiography. Diabetes mellitus was present in 123 patients (46%). The most common target vessel for PCI was left anterior descending artery (43%) followed by right coronary artery (36%), left circumflex (10%) and left main (6%). The majority of lesions were type B-C (85%) by ACC/AHA lesion classification. An average of 1.25 ± 0.5 AES were used per patient, with mean AES diameter of 3.1 ± 0.4 mm and average total length of 34.8 ± 19.4 mm. At 12-month follow-up, 4% of patients developed MACE. MACE was mainly driven by cardiovascular mortality (1.5%), MI (2%) and TLR (1.5%). The rate of stent thrombosis was 1.5%. Conclusion: In a contemporary all-comers South-East Asian registry with high rate of diabetes mellitus, AES was found to be efficacious with a low incidence of MACE observed at 12-month follow-up.